Manajemen Pembelajaran Bagi Anak Tunanetra di SLB TPI ABC Medan - Sabtina , Desi; Nasution , Rizky Amanda; Rahayu , Putri; Hafis, Bilal (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to describe and analyze the implementation of inclusive education for blind children at SLB TPI ABC Medan. Three main aspects were studied, including the implementation of learning at TPI ABC Medan, inhibiting, and supporting factors in the learning process, and evaluation of learning outcomes. This research is a type of qualitative research. Data for this research was obtained through direct observation and interviews. The data analysis technique used is Purposive Sampling, namely a data analysis technique by providing several appropriate criteria for sources. The results of this research show that the implementation of learning at TPI ABC Medan is carried out individually. Teachers have a more dominant role in the learning process. Learning is carried out using special learning media and with methods adapted to students' needs. The thing that hinders learning for children with special needs who are blind is that learning media is still limited, making the learning process less than optimal. What supports the learning process is that students have strong learning motivation and teachers are also experts in their fields. To see the learning outcomes of the blind crew, the teacher carried out an evaluation by giving assignments in the form of essays or multiple choices that were adapted to the learning material.